Pelatihan Pencatatan Transasksi Keuangan Untuk BUMDES Pada BUMKUTE Mekar Jaya, Desa Tanoh Alas, Kecamatan Babul Makmur, Kabupaten Aceh Tenggara - Jaka Syahputra; Sanjaya Alacsel; Tri Rasyid Desky (Nusantara Mengabdi Kepada Negeri, 2024)
From the results of the evaluation carried out on the training participants, the training participants participated in the event enthusiastically, this was seen from the beginning to the end of the event, all participants participated well, it was also seen in the question and answer session where all the training participants' problems were related to recording techniques and journal corrections, the aim of Community Service activities (PKM) in this community have been achieved well and in accordance with the stated objectives and the operation of the Labamu application has been successfully answered and provided direct guidance by the service team. Recommendations for follow-up activities are to focus more on different types of business from each BUMDes Unit. Mentoring can be carried out per group according to the participants' business base so that implementation is more effective and easier. The methods used for community service activities are (1) lectures and training on the use of the 'SIAPIK' application in conveying the concept of effective transaction recording for Village-Owned Enterprises and (2) case questions to provide examples of transaction recording practices and correction journals for transaction treatment note-taking errors, and (3) providing consultation and assistance in the field. The results of the evaluation of this service activity showed that participants' level of understanding of the material provided was 80%.